Impacting Technology Integration in the Classroom Through Professional Development - West, Laura D. (Valdosta State University, 2005)
The purpose of this study was to determine if providing professional development to teachers on how to use technology and how to integrate technology into the curriculum would increase the use of technology in the classroom. Twenty-one elementary school faculty members participated in two professional development workshops to integrate technology into their lessons. Ongoing assistance in using technology and helping teachers to integrate technology into the curriculum was provided over a 3-week time span. Data collection instruments included pre/post surveys on teacher technology skill levels, confidence levels, and the extent to which they integrate technology into the curriculum. Technology journals provided insight into the teacher experiences and concerns with technology. A technology log demonstrated how often the technology was used and how it was used. A questionnaire and an interview provided additional information into teachers' thoughts about professional development. Eight participants completed the interview questions. Results of the follow-up survey indicate that teachers' confidence level, skill level, and technology integration competencies increased after participating in the professional development intervention. Participants indicated that staff development was necessary for technology integration. The results of the study were communicated to the learning community through a meeting with teachers and administrators. That meeting supported continuation of staff development workshops on other available technologies as well as on-going support by the media specialist.
Keywords: technology; curriculum; classroom; Educational technology; Teaching--Aids and devices; Computer-assisted instruction